The evolution of media education in the UK: some lessons from history - Buckingham, David (Comunicação & Educação, 2016)
Media education in the UK has a long history, and has been an established element of the school curriculum for around 25 years. However, in the past decade it has faced increasing challenges. In this article, we want to explain these developments, not least in the hope that educators might avoid some of the obstacles we have encountered. In doing so, we hope to present the history of media education not just as a succession of ideas, but also to explain why particular educational approaches have arisen in particular historical circumstances.